2022
DOI: 10.3390/nu14122466
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Micronutrient Intake Is Associated with the Risk of Periodontitis: A Dose–response Association Study Based on NHANES 2009–2014

Abstract: The association between micronutrient intake and the risk of periodontitis has received much attention in recent years. However, most studies focused on the linear relationship between them. This study aimed to explore the dose–response association between micronutrient intake and periodontitis. A total of 8959 participants who underwent a periodontal examination, and reported their micronutrient intake levels were derived from the US National Health and Nutrition Examination Survey (NHANES, 2009–2014) databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 85 publications
1
26
0
Order By: Relevance
“…A novel feature of this study is that we found a non-linear association between GNRI levels and the risk of periodontitis and mortality in patients with periodontitis. Our results also show for the rst time that PEM may be associated with a lower risk of periodontitis and a lower risk of death in patients with periodontitis, are consistent with those of previous studies on the association between nutritional intake and periodontitis [24][25][26][27][28].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…A novel feature of this study is that we found a non-linear association between GNRI levels and the risk of periodontitis and mortality in patients with periodontitis. Our results also show for the rst time that PEM may be associated with a lower risk of periodontitis and a lower risk of death in patients with periodontitis, are consistent with those of previous studies on the association between nutritional intake and periodontitis [24][25][26][27][28].…”
Section: Discussionsupporting
confidence: 92%
“…We referred to the consensus recommendations of the CDC and the American Academy of Periodontology Prevention for epidemiological studies on the diagnosis of periodontitis [32]. In the present study, we assessed moderate and severe periodontitis as a category of periodontitis, with mild periodontitis and no periodontitis placed in another category to eliminate the potential risk of bias due to the possible overprevalence of mild periodontitis [27,33]. Moderate/severe periodontitis was de ned as follows:…”
Section: Periodontal Examinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress is a hallmark of periodontitis, and multiple antioxidant nutrients can potentially improve periodontal conditions by enhancing antioxidant defence and diminishing oxidative stress (Chapple & Matthews, 2007). Specifically, individuals with a low intake of vitamins A, C and E are at greater risk of developing periodontitis (Lee et al, 2017; Li, Shang, et al, 2022; Li, Song, & Chen, 2022). However, assessing the diet's overall antioxidant characteristics is challenging based on a single antioxidant.…”
Section: Introductionmentioning
confidence: 99%
“…Periodontitis is a common inflammatory disease that causes destruction of soft and hard periodontal tissues, leading to tooth mobility and loss (Li et al, 2021(Li et al, , 2022Pihlstrom et al, 2005). The disease is initiated by a dysbiotic microbial community, within which different microbial members or specific gene combinations have distinct roles that synergize to shape a disease-causing microbiota.…”
Section: Introductionmentioning
confidence: 99%